Pengaruh Online Customer Review, Food Influencer dan Content Marketing terhadap Tingkat Kunjungan Bakso Mas Roy Cabang Surabaya Timur - Devi Khoiriyah; Ety Dwi Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of online customer reviews, food influencers, and content marketing on the level of customer visits at Bakso Mas Roy East Surabaya Branch. The research was carried out using quantitative methods with an associative approach, the population used was all customers of the East Surabaya branch of Mas Roy meatballs. A sample of 194 respondents who were met by the author at the research location, these results were obtained using the Slovin formula. The research results show that the online customer review variable (X1) is 0.000 < 0.05. t-calculated value -3.812 < t table 1.972 So H1 is accepted, meaning that the online customer review variable has a partially negative effect on the level of customer visits from Bakso Mas Roy. on the food influencer variable (X2) it is 0.001 < 0.05. The calculated t value is 3.320 > t table 1.972. So H2 is accepted, meaning that the food influencer variable partially influences the level of visits. content marketing variable (X3) is 0.000 < 0.05. The calculated t value is 3.947 > t table 1.972. So H0 is rejected and H3 is accepted, meaning that the content marketing variable partially influences the level of visits.